2019
DOI: 10.25165/j.ijabe.20191203.4227
|View full text |Cite
|
Sign up to set email alerts
|

Developing a screw conveyor in radio frequency systems to improve heating uniformity in granular products

Abstract: Radio frequency (RF) treatments have been increasingly studied due to the rapid heating, deep power penetration depth and high energy efficiency. However, the major challenges for commercial RF applications are non-uniform and runaway heating. The purpose of this study was to improve RF heating uniformity in three granular products (soybean, corn, and peanut) using a custom-made screw conveyor with sample movement and mixing. The results showed that soybean, corn and peanut samples in the screw conveyor were R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Rotating treatment made the value of heating uniformity index scattered within 0.027 ± 0.002 and 0.041 ± 0.007. Movement and mixing operations of food materials could improve heating uniformity effectively (Bedane et al., 2017; Zheng et al., 2016; Zhou & Wang, 2019). The movement of pea grains in rotating container including horizontal and vertical spatial motion and therefore the uniformity of RF heating was significantly improved.…”
Section: Resultsmentioning
confidence: 99%
“…Rotating treatment made the value of heating uniformity index scattered within 0.027 ± 0.002 and 0.041 ± 0.007. Movement and mixing operations of food materials could improve heating uniformity effectively (Bedane et al., 2017; Zheng et al., 2016; Zhou & Wang, 2019). The movement of pea grains in rotating container including horizontal and vertical spatial motion and therefore the uniformity of RF heating was significantly improved.…”
Section: Resultsmentioning
confidence: 99%
“…Diagram of assistance devices used in RF system, including a rotation device adapted from Hao et al . (2021) (a), an inclined conveyor with turntable adapted from Palazoglu & Miran (2018) (b), and a screw conveyor adapted from Zhou & Wang (2019) (c).…”
Section: Applications Of Rf Pasteurisation Treatment For Seedsmentioning
confidence: 99%
“…They showed that the average movement speed of the particles depends on the frequency and amplitude values of the frequency. Other studies with mechanical vibration affecting screw conveyors [9][10][11][12] can also be examined.…”
Section: Introductionmentioning
confidence: 99%